Tool for extracting and visualizing travel patterns - Tan, Ying Ting (2014)
There are 7.7 million new cases of dementia each year. This means that every 4 seconds, there is someone in the world diagnosed with dementia [1]. With such a rapid increasing number of Dementia patients, there is a high demand to carry out research to study on Dementia and find ways to save their life. The project aims to implement a visualization tool to aid researchers to study the travel patterns. As this is a continuation project, the basic functionalities of the tool were already implemented. However, it is still very limited in the number of features the program can do. The purpose of this project is to continue the unfinished work and further enhance the tool.